2017
DOI: 10.2134/agronj2016.08.0468
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for Measuring Feces Ammonia‐Nitrogen and Carbon Dioxide‐Carbon Emissions and Decomposition Rate Constants

Abstract: A rapid approach is needed for determining the eff ectiveness of precision conservation on soil health as evaluated using CO 2 and NH 3 emissions. Th is study demonstrated an approach for calculating CO 2 -C and NH 3 -N emissions and associated rate constants when feces were applied to bare soil or soil + vegetation. In addition, point CO 2 -C emission measurements were compared with near continuous measurements. Th e CO 2 -C emissions were measured at 2 h intervals over 20 d, whereas ammonia volatilization wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…For example, Chang et al. (2017) demonstrated that increasing the soil temperature from 15 to 23 °C increased N 2 O–N emissions nearly sevenfold, from 0.47 to 2.77 kg N ha −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Chang et al. (2017) demonstrated that increasing the soil temperature from 15 to 23 °C increased N 2 O–N emissions nearly sevenfold, from 0.47 to 2.77 kg N ha −1 .…”
Section: Resultsmentioning
confidence: 99%
“…Temperature differences among the productivity zones can alter GHG emissions by influencing microbial activity and N 2 O solubility. For example, Chang et al (2017) demonstrated that increasing the soil temperature from 15 to 23˚C increased N 2 O-N emissions nearly sevenfold, from 0.47 to 2.77 kg N ha −1 .…”
Section: Climatic Conditions and Plant Yieldsmentioning
confidence: 99%
“…In spite of these difficulties, obtaining accurate information is critical for estimating the carbon footprint for the entire watershed. One approach to overcome these barriers to conduct research at targeted locations and then using mathematics or a simulation model to calculate area corrected emission estimates (Chang, Clay, Clay, Smart, & Ohrtman, 2017).…”
Section: Findings Relative To Ipcc N 2 O Default Value Of 1% Of Applimentioning
confidence: 99%
“…However, in the NGP, grazing‐related soil compaction is not typical because the annual freeze/thaw and wet/dry cycles can reduce this risk (Liebig et al, 2012). Further, livestock waste (feces and urine) returns organic matter and nutrients to the soil, which build the soil structure (Chang et al, 2017; Haynes and Williams, 1993; Soussana et al, 2004).…”
Section: Impacts Of Integrated Crop–livestock Systems On Crop Productmentioning
confidence: 99%